Reproductive migration and population dynamics of the blue crab Callinectes danae in an estuary in southeastern Brazil - Sant'Anna, Bruno Sampaio [UNESP]; Turra, Alexander; Zara, Fernando Jose [UNESP] (Taylor & Francis As, 2012)
Portunid crabs are an important resource in estuaries, and require appropriate management to guarantee their long-term availability. We investigated the population dynamics and reproduction of Callinectes danae in the Estuarine-Bay Complex of Sao Vicente, São Paulo, Brazil, to provide basic biological information for public policies for the management of this fishery. Monthly samples were obtained from March 2007 to February 2008 on eight transects, four in the estuary and four in the bay. A total of 2261 specimens (403 males, 1288 females, of which 570 were ovigerous) were collected. Males were significantly larger than females, and the size-frequency distribution was unimodal for males, females and ovigerous females. The sex ratio was nearly always skewed toward females (M:F - 1:4.6). C. danae showed seasonal-continuous reproduction, with high reproductive activity in the warmer season. C. danae breeds in the estuarine-bay complex, with males and juvenile females concentrated in the estuary. After copulation, fertilized females migrate to the estuary entrance and the bay, where ovigerous females are commonly found spawning in high-salinity areas. Therefore, to manage this important economic resource, both the estuary and the bay should be considered for protection, but special attention should be given to the estuary entrance during the summer months, when ovigerous females concentrate.
Keywords: Callinectes danae; migration; Portunidae; population dynamics; reproduction